Nitric Oxide and Mechano-Electrical Transduction in Cardiomyocytes - Boycott, Hannah E.; Nguyen, My-Nhan; Vrellaku, Besarte; Gehmlich, Katja; Robinson, Paul (Frontiers in Physiology, 2020)
The ability of the heart to adapt to changes in the mechanical environment is critical for normal cardiac physiology. The role of nitric oxide as a mediator of mechanical signalling has become increasingly recognised. Produced in the heart by nitric oxide synthases, nitric oxide affects almost all mechanotransduction pathways within the cardiomyocyte, with roles mediating mechanosensing, mechano-electric feedback (via modulation of ion channel activity) and calcium handling. In this review we focus on the key role of nitric oxide in regulating these processes and highlight areas in which further research is needed. The dysfunction of these processes is likely to be a feature of cardiac pathology (e.g. atrial fibrillation, cardiomyopathy and heart failure) and a better understanding of the importance of nitric oxide signalling and its links to mechanical regulation of heart function may advance our understanding of these conditions.